Financial Feasibility Analysis (Case Study of Tunas Maru Catfish Enlargement Business in Poasia District Kendari City) - Fofo Sesario; Abdi Abdi; Wa Ode Yusria (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This research aims to determine the financial feasibility and sensitivity of the catfish enlargement business in the Poasia District of Kendari City from a financial perspective. This research was conducted in the Poasia District of Kendari City from August 2021 to April 2022. The object of this study is the Tunas Maru catfish enlargement business. The study uses case study methods with quantitative data analysis. This research aims to determine the feasibility of catfish enlargement businesses in terms of financial aspects. Financial aspects are analyzed using the present net method value. Net B/C Ratio, Internal Rate Of Return, Payback Period, and Sensitivity Analysis. The data used in this study are primary and secondary. This study's results obtained the value of NPV =52.364.673, Net B / C = 39,3, IRR = 52%, and Payback Period = 2 years 5 months. This business is worth working on financially. In addition, based on the calculation of sensitivity analysis, the effort of catfish enlargement remains feasible for a 10% decrease in production.